Antifungal evaluation of turmeric rhizome extract against Colletotrichum capsici, the causal agent of anthracnose on red-chili peppers (Capsicum annuum L.) - Akin, Hasriadi Mat; Anggraini, Desma; Wibowo, Lestari; Prasetyo, Joko; Suharjo, Radix (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
This study was conducted to evaluate the antifungal activity of the ethanolic extract of turmeric rhizome against Colletotrichum capsici Syd. and its efficacy in reducing anthracnose disease development on red chili peppers. The in vitro experiment aimed to determine the effect of the extract on inhibiting C. capsici growth in potato sucrose agar (PSA) medium incorporating the turmeric rhizome extract. The variables examined were mycelial growth, fungal sporulation, and spore germination. The in vivo experiment aimed to evaluate the effectiveness of the extract in reducing disease development on red chili peppers. The treatments were conducted using a completely randomized design with five concentration treatments and three replicates. The variables examined were radial mycelial growth zone diameter, fungal sporulation, spore germination, and disease intensity. Data were analyzed by analysis of variance, and the least significant difference was used for comparing means between treatments. The results of these experiments showed that ethanolic turmeric rhizome extract exhibited antifungal activity against C. capsici both in vitro and in vivo conditions. Turmeric rhizome extracts with concentrations of 1%, 2%, 3%, and 4% significantly inhibited mycelial growth, and even at a 4% concentration, C. capsici fungal colonies did not grow. Evaluation of the effect of the extract on fungal sporulation showed that inhibition occurred at a concentration of 3%, while inhibition of spore germination occurred at concentrations of 1%, 2%, and 3%. Application of turmeric extract at concentrations of 1%, 2%, 3%, and 4% effectively reduced the intensity of anthracnose on red chili. Read correction >